The effectiveness of integrating mobile devices with inquiry-based learning on students' learning achievements: a meta-analysis. (2018) - Zheng, Lanqin; Li, Xin; Tian, Lu; Cui, Panpan
Mobile devices are gaining more and more popularity in recent years. Researchers and practitioners took advantages of mobile devices to facilitate inquiry-based learning in the past decade. Although there were many studies that using mobile devices in inquiry-based learning, the systematic review of the effectiveness of integrating mobile devices with inquiry-based learning remained lacking. This meta-analysis examined 34 empirical studies with 2316 participants on integrating mobile devices with inquiry-based learning from 2007 to 2016. The results indicated that there was a high effect size of 0.91 for the application of mobile devices in improving students' learning achievements. The features of moderator variables were also deeply analysed and synthesised based on the content analysis of all studies. The results together with the implications for practices and research were also discussed in detail.